2013
DOI: 10.1007/s11033-013-2912-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of FcγRIIB and FcγRIIA R131H gene polymorphisms with renal involvement in Egyptian systemic lupus erythematosus patients

Abstract: Identification of the genetic basis of systemic lupus erythematosus (SLE) may contribute to the discovery of effective drugs before renal involvement. Our aim of this study was to estimate the association between Fc gamma receptor (FcγR) polymorphisms and SLE and renal involvement in Egyptian patients. FcγRIIB and FcγRIIA R131H gene polymorphisms were genotyped in 180 Egyptian adults. Genotyping for FcγRIIA R131H was performed using allele-specific PCR and FcγRIIB-Ile232 Thr polymorphism was genotyped using po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In congruency with previous reports (Vlachoyiannopoulos et al, 1996;Luyckx et al, 2005;Somarelli et al, 2011;Watanabe et al, 2012;Gunnarsson et al, 2013;Zidan et al, 2013), the analysis of 187 medical records documented for SLE and MCTD patients revealed that 35 clinical manifestations and molecular features are significantly different in the two disease states (Figure 8). The prevalence of skin rashes in SLE while myositis and muscle weakness was presented in MCTD was expected since these are typical clinical manifestation associated with each of these autoimmune illnesses (Uthman et al, 1996;Belibou et al, 2012;Szodoray et al, 2012).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In congruency with previous reports (Vlachoyiannopoulos et al, 1996;Luyckx et al, 2005;Somarelli et al, 2011;Watanabe et al, 2012;Gunnarsson et al, 2013;Zidan et al, 2013), the analysis of 187 medical records documented for SLE and MCTD patients revealed that 35 clinical manifestations and molecular features are significantly different in the two disease states (Figure 8). The prevalence of skin rashes in SLE while myositis and muscle weakness was presented in MCTD was expected since these are typical clinical manifestation associated with each of these autoimmune illnesses (Uthman et al, 1996;Belibou et al, 2012;Szodoray et al, 2012).…”
Section: Discussionsupporting
confidence: 67%
“…Given that these results and others have identified specific organ involvement in either SLE or MCTD patients (Figure 8) (Vlachoyiannopoulos et al, 1996;Luyckx et al, 2005;Watanabe et al, 2012;Gunnarsson et al, 2013;Zidan et al, 2013), it highlights the clinical value of MCTD diagnosis given that the type of medical regime delivered to a patient will rely on the potential development of specific organ(s) malfunction. Aware of the lack of methods designed to segregate between these autoimmune disorders (Table 6 and Figure 11), we described eight different novel classification rules (Tables 3 and 4 represents the best classifier from those evaluated with a power of 93% to distinguish between SLE and MCTD patients (Figure 12).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Polymorphisms in these receptors have been associated with infectious diseases and autoimmunity (Zidan, Sabbah et al 2013). Genotyping of 80 GBS patients and 80 healthy controls from North India found that polymorphisms in genes encoding FcγRIIA and FCγRIIIA, but not FcγRIIIB, were associated with GBS (Geleijns, Emonts et al 2007).…”
Section: Fc Receptorsmentioning
confidence: 99%